Rethinking welfare : a critical perspective - Ferguson, Iain, 1954- (SAGE, 2002)
The anti-capitalist movement is increasingly challenging the global hegemony of neo-liberalism. The arguments against the neo-liberal agenda are clearly articulated in 'Rethinking Welfare'.